The heart rate on admission was associated with the mortality in elderly patients with hip fractures: a retrospective cohort study from a trauma centre in northwestern China - Zhi Yang; Wei-Song Zhang; Shao-Hua Chen; Bin-Fei Zhang (BMJ Open)
Objectives To evaluate the association between heart rate on admission and mortality in elderly patients with hip fractures.Design A retrospective cohort study.Setting At a trauma centre in northwestern China.Participants Elderly patients with hip fractures.Results This cohort study included 2006 patients who met the study criteria. The mean heart rate at admission was 81.77±15.63 beats per minute. During follow-up, 189 patients died for all-cause reasons in 1 year. Age, coronary heart disease, cancer, dementia and time to operation were introduced in multivariate regression analysis. Multivariate logistic regression showed that heart rate was associated with mortality in geriatric patients with hip fracture (OR=1.01, 95% CI 1.00 to 1.02, p=0.0242). However, the linear association was unstable, and we found a nonlinear one. In the nonlinear association, the inflection point was 84 beats per minute. If below this threshold, each 1 beat per minute increase in heart rate was associated with a 4% increase in the risk of death (OR=1.04, 95% CI 1.01 to 1.06, p=0.0017). If greater than this threshold, the risk of death peaked and was not associated with the heart rate (OR=1.00, 95% CI 0.98 to 1.01, p=0.6691).Conclusion In conclusion, the heart rate was nonlinearly associated with 1-year mortality in geriatric patients with hip fractures. The low heart rate on admission was associated with low 1-year mortality. When the heart rate was over 84 beats per minute, the risk of death peaked, and there was no association with heart rate anymore.Trial registration number This study was registered on the website of the Chinese Clinical Trial Registry (ChiCTR: ChiCTR2200057323).